Identifying the Factors of a Happy Worker: Case of Private Banks of Bangladesh - Tasnim, Zerin; Hasnain, Afreen Ahmad (Global Disclosure of Economics and Business, 2016)
A happy worker at workplace has a direct impact on the overall quality of his/her life and therefore it’s very important to understand what makes us happy or unhappy at work. Also a happy worker is an important factor for all organizations development and to enhance its productivity. A company should focus on workers to be happy because of their own improvement. But, surprisingly, there is an absence of sound framework for understanding such an important issue from both workers’ and organization’s perspective. This study focus on various kinds of workplaces of Bangladesh and for this purpose a survey is done among 200 employees of six private banks within both male and female employees. The present study focuses on five particular phenomena related to identify the dimensions of a happy worker as psychological wellbeing, peer behavior, work family conciliation, work stress, management cooperation and personal development.